Young star clusters inmersed in intermediate-age fields in the Large Magellanic Cloud bar - Piatti, Andres Eduardo (2003)
We present Washington system photometry for 11 star cllusters inmersed in the north-west part of the Large Magellanic Cloud (LMC) bar, centred on the intermediate-age clusters NGC 1865 and SL 244. The fields are heavely populated by the intermediate-age component of the LMC bar. We succedded in disentangling cluster colour-magnitude diagrams from those of the fields and in deriving reddening and ages for five clusters - SL 218, BRHT4b, and NGC 1839, 1838 and 1863 - with the aid of recent Washington system theoretical isochrones. The resulting cluster ages range between 50 and 125 Myr. Despite their proximity, NGC 1836 and BRHT4b have very different ages. Thus the possibility of these two objects being a binary cluster is very unlikely, although a capture cannot be ruled out a priori. Our results suggest that for each intermediate-age cluster remaining in the LMC bar region, a number of robust young blue star clusters occur in the same region.